CONSERVATION OF COCONUT TREE sap (COCOS NUCIFERA) BASED ON THE IMPACT ON HEALTH AND THE WAY OF PRODUCTION IN TAROK VILLAGE, SUB-DISTRICT 2 X 11 KAYU TAMAN - Febrianto Febrianto; Karina Netashia (Pendidikan IPA, FMIPA, UNP, 2021)
jurnal tuak